2014
DOI: 10.1177/0022034514535807
|View full text |Cite
|
Sign up to set email alerts
|

Lubricin is Required for the Structural Integrity and Post-natal Maintenance of TMJ

Abstract: The Proteoglycan 4 (Prg4) product lubricin plays essential roles in boundary lubrication and movement in limb synovial joints, but its roles in temporomandibular joint (TMJ) are unclear. Thus, we characterized the TMJ phenotype in wild-type and Prg4 -/-mouse littermates over age. As early as 2 weeks of age, mutant mice exhibited hyperplasia in the glenoid fossa articular cartilage, articular disc, and synovial membrane. By 1 month of age, there were fewer condylar superficial tenascin-C/ Col1-positive cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 31 publications
6
43
0
2
Order By: Relevance
“…It has previously been reported, using standard histology, that lubricin knockout mice develop age-related abnormalities in their TMJs, including widening and flattening of condylar surface with superficial chondrocyte loss189. Our confocal imaging detected these same changes in Prg4 knockout mice without requiring decalcification, paraffin embedding, sectioning, and staining (Fig.…”
Section: Resultssupporting
confidence: 74%
“…It has previously been reported, using standard histology, that lubricin knockout mice develop age-related abnormalities in their TMJs, including widening and flattening of condylar surface with superficial chondrocyte loss189. Our confocal imaging detected these same changes in Prg4 knockout mice without requiring decalcification, paraffin embedding, sectioning, and staining (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Notably, Prg4- null mice also displayed characteristic features of degenerative changes in TMJs including articular surface deterioration, loss of disc concave-convex morphology, synovial membrane hyperplasia and protein deposition. (Hill et al, 2014; Koyama et al, 2014). We also reported that Prg4 -null mice displayed increased levels of chondrogenesis and ectopic cartilage formation within TMJ components (Bechtold et al, 2015; Koyama et al, 2014), but the cellular, signaling and molecular mechanisms underling such potentially important pathogenic transformation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of SZP in the knee joint is synthesized by the superficial zone articular cartilage and synovium (Schumacher et al, 1999), cells in the meniscus (Schumacher et al, 2005), tendon (Rees et al, 2002), ligament (Lee et al, 2008b; Zhang et al, 2011), and infrapatellar fat pad (Lee et al, 2008a) produce SZP as well. SZP has also been demonstrated to be expressed by, and lubricate, the eye lid-corneal interface (Cheriyan et al, 2011; Schmidt et al, 2013), intervertebral disc (Shine et al, 2009), and temporomandibular joint (TMJ) (Koyama et al, 2014; Wei et al, 2010). While the source is unknown, SZP is additionally present in whole blood, plasma, serum, and platelet-rich plasma (Sakata et al, 2015; Su et al, 2001).…”
Section: Introductionmentioning
confidence: 99%